A Phase 2 Randomised Clinical Trial Assessing the Tolerability of Two Different Ratios of Medicinal Cannabis in Patients With High Grade Gliomas - Schloss, Janet; Lacey, Judith; Sinclair, Justin; Steel, Amie; Sughrue, Michael; Sibbritt, David; Teo, Charles (Frontiers in Oncology, 2021)
Background Cannabis for cancer is very topical and, given the use of illicit cannabis preparations used in this vulnerable population, research investigating standardised, quality-assured medicinal cannabis is critical to inform clinicians and assist patient safety. Methods A randomized trial involving adult patients diagnosed with a high-grade glioma, no history of substance abuse, liver or kidney damage or myocardial infarction were eligible for inclusion in a tolerability study on two different ratios of medicinal cannabis. Baseline screening of brain morphology, blood pathology, functional status, and cognition was conducted. A retrospective control group was used for comparison for secondary outcomes. Results Participants (n=88) were on average 53.3 years old. A paired t-test assessed the Functional Assessment of Cancer Therapy for Brain Cancer (FACT-Br) between groups from baseline to week 12 found that the 1:1 ratio favoured both physical (p=0.025) and functional (p=0.014) capacity and improved sleep (p=0.009). Analysis of changes from baseline to week 12 also found 11% of 61 participants had a reduction in disease, 34% were stable, 16% had slight enhancement, and 10% had progressive disease. No serious adverse events occurred. Side effects included dry mouth, tiredness at night, dizziness, drowsiness. Conclusion This study demonstrated that a single nightly dose of THC-containing medicinal cannabis was safe, had no serious adverse effects and was well tolerated in patients. Medicinal cannabis significantly improved sleep, functional wellbeing and quality of life. Trial registration The trial is registered on the Australian New Zealand Clinical Trials Registry (ANZCTR), registration number ACTRN12617001287325. http://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=373556&isReview=true